3D-Printed MOF Monoliths: Fabrication Strategies and Environmental Applications - Molavi, Hossein; Mirzaei, Kamyar; Barjasteh, Mahdi; Rahnamaee, Seyed Yahya; Saeedi, Somayeh; Hassanpouryouzband, Aliakbar; Rezakazemi, Mashallah (Nano-Micro Letters, 2024)
Metal–organic frameworks (MOFs) have been extensively considered as one of the most promising types of porous and crystalline organic–inorganic materials, thanks to their large specific surface area, high porosity, tailorable structures and compositions, diverse functionalities, and well-controlled pore/size distribution. However, most developed MOFs are in powder forms, which still have some technical challenges, including abrasion, dustiness, low packing densities, clogging, mass/heat transfer limitation, environmental pollution, and mechanical instability during the packing process, that restrict their applicability in industrial applications. Therefore, in recent years, attention has focused on techniques to convert MOF powders into macroscopic materials like beads, membranes, monoliths, gel/sponges, and nanofibers to overcome these challenges.Three-dimensional (3D) printing technology has achieved much interest because it can produce many high-resolution macroscopic frameworks with complex shapes and geometries from digital models. Therefore, this review summarizes the combination of different 3D printing strategies with MOFs and MOF-based materials for fabricating 3D-printed MOF monoliths and their environmental applications, emphasizing water treatment and gas adsorption/separation applications. Herein, the various strategies for the fabrication of 3D-printed MOF monoliths, such as direct ink writing, seed-assisted in-situ growth, coordination replication from solid precursors, matrix incorporation, selective laser sintering, and digital light processing, are described with the relevant examples. Finally, future directions and challenges of 3D-printed MOF monoliths are also presented to better plan future trajectories in the shaping of MOF materials with improved control over the structure, composition, and textural properties of 3D-printed MOF monoliths. Highlights: 1 Challenges and future directions for 3D-printed metal-organic frameworks (MOFs) monoliths in environmental applications are discussed. 2 Various strategies for fabrication of 3D-printed MOF monoliths are summarized. 3 Advancements in 3D printing enable customizable and high-performance MOF monoliths. 4 3D orienting of MOFs opens avenues for applications in water treatment and gas adsorption.